Comparison of Hereford steers sired by small, medium and large size bulls. - Weber, A.D.; Pickett, A.G.; Mackintosh, D.L. (Kansas Agricultural Experiment Station, 2012)
The Kansas, Oklahoma, and Ohio Agricultural Experiment Stations are cooperating in this study, which is supported by grants from the American Hereford Association. In October, 1948, each station received 96 steer calves from the following commercial herds: Bar 13 Ranch, P. K. Ranch, and O. M. Wallop, Sheridan, Wyoming; and M. C. Simpson, Volborg, Montana. These steer calves, sired by small, medium, and large size bulls are being compared at each of the three stations under three standard systems of feeding and management. System I involves immediate full feeding for 225 days. System II represents a deferred full feeding program in which the steers calves are wintered well, grazed without grain from May 1 to August 1, and then full fed in dry lot 100 days. System III has for its objective the production of two-year old grass fat steers without the feeding of grain. Phases under this system include: wintering as calves without grain; grazing as yearlings a full season without supplemental feed; wintering as yearlings without grain; grazing as two-year olds without supplemental feed and selling as slaughter cattle directly off pasture.
Keywords: Beef; Steers; Bull size